Using Behavioral Mapping to Examine the Validity of the IPIP-IPC. (April 2013) - Markey, Patrick; Anderson, Juliene M.; Markey, Charlotte
Behavioral mapping, a method designed to relate behaviors to circumplex models, was used to examine the predictive validity of the International Personality Item Pool–Interpersonal Circumplex (IPIP-IPC). In this study, 96 participants first completed the IPIP-IPC and then were videotaped in a social interaction with a confederate. At the conclusion of this interaction, the Riverside Behavioral Q-Sort was used to code 64 different behaviors expressed by the participants. Results indicated that participants' Riverside Behavioral Q-Sort interpersonal behaviors occurred in a manner predicted by their IPIP-IPC scores. Such findings suggest that the IPIP-IPC can predict a multitude of interpersonal behaviors expressed during a dyadic interaction.